Modulators of radiation-induced cardiopulmonary toxicities for non-small cell lung cancer: Integrated cytokines, single nucleotide variants, and HBP systems imaging - Mukai-Sasaki, Yuki; Liao, Zhongxing; Yang, David; Inoue, Tomio (Frontiers in Oncology, 2022)
Radiation therapy (RT)-induced cardiopulmonary toxicities remain dose-limiting toxicities for patients receiving radiation therapy to the thorax, especially for lung cancer. Means of monitoring and predicting for those receiving RT or concurrent chemoradiation therapy before treatment begins in individual patients could benefit early intervention to prevent or minimize RT-induced side effects. Another aspect of an individual’s susceptibility to the adverse effects of thoracic irradiation is the immune system, as reflected by phenotypic factors (patterns of cytokine expressions), genotypic factors (single nucleotide variants SNVs; formerly single nucleotide polymorphisms [SNPs]), and aspects of quantitative cellular imaging. Levels of transcription, production, and functional activity of cytokines are often influenced by SNVs that affect coding regions in the promoter or regulatory regions of cytokine genes. SNVs can also lead to changes in the expression of the inflammatory cytokines, interferons (IL-6, IL-17) and tumor necrosis factors (TNF-α) at the protein level. RT-induced cardiopulmonary toxicities could be quantified by the uptake of 18F-fluorodeoxyglucose (FDG), however, FDG is a sensitive but not specific biomarker for differential diagnosis between inflammation/infection and tumor recurrence. FDG is suitable for initial diagnosis of predisposed tissue injuries in non-small cell lung cancer (NSCLC). 99mTc-EC-glucosamine (99mTc-EC-G), a N-acetylglucosamine analogue, measures tumor DNA-damage response via hexosamine biosynthetic pathways (HBP). 99mTc-EC-G is more specific than FDG in tumor staging, re-staging, radiotherapy dose, chemotherapy doses, and patient selection for HBP-directed optimal outcome. The correlative analyses of circulating pro-inflammatory cytokines, genotype SNVs, and cellular imaging that improve the diagnosis, prognosis, monitoring, and prediction of RT-induced cardiopulmonary toxicities in NSCLC are reviewed.